Answer: [tex]x=-3[/tex]
Simplify both sides of the equation
[tex]1+-2x=-1+8+8x+-8x[/tex]
[tex]-2x+1=(8x+-8x)+(-1+8)[/tex] (Combine Like Terms)
[tex]-2x+1=7[/tex]
Subtract 1 from both sides
[tex]-2x+1-1=7-1\\-2x=6[/tex]
Divide both sides by -2
[tex]-2x/-2=6/-2\\x=-3[/tex]
Answer:
[tex]\Huge \boxed{x=-3}[/tex]
Step-by-step explanation:
[tex]1-2x= -1+8+8x-8x[/tex]
Combining like terms.
[tex]1-2x= 7[/tex]
Subtracting 1 from both sides.
[tex]-2x= 7-1[/tex]
[tex]-2x=6[/tex]
Dividing both sides by -2.
[tex]x=-3[/tex]